ANALYSIS OF MERCURY SOIL GAS FOR GEOTHERMAL POTENTIAL ZONE DELINEATION IN THE PATUHA GEOTHERMAL FIELD, KECAMATAN CIWIDEY, KABUPATEN BANDUNG - Abyan Ilmanto, Ahmad
The issue of global warming must be responded immediately by reducing carbon emissions. But in Indonesia, the main energy needs are mostly fulfilled by using fossil fuels such as petroleum and coal. The use of geothermal energy is an alternative to clean and renewable energy to answer the problems arising from carbon emissions. Geothermal energy is one of the New Renewable Energy (EBT) which can be used as an alternative to fossil energy. Based on the 2016 Energy Outlook data that have been published by the National Energy Board, the utilization of EBT is projected to increase until 2050. One of the prospecting methods for finding geothermal potential zones is with mercury in soil-gas. Mercury in soil-gas is one of the preliminary exploration methods which is relatively inexpensive and effective for detecting geothermal reservoirs. The data of concentration of mercury in soil-gas were collected in eighteen test wells in the Patuha Geothermal Field around the operating area of PT Geodipa Energi. Delineation of geothermal potential zones in the Patuha geothermal field is done by correlating the spatial distribution of mercury gas concentrations with local geological structures and rock lithology. The study was conducted from April to August 2019 where five measurements of mercury gas concentrations were accomplished. The measurements produced a high spatial distribution of mercury concentrations at the point PPL06 (32.41 ng / m3), PA03 (15.45 ng / m3), and PA04 (13.18 ng / m3). After correlating it with lithology and geological structure, it is found that there is no influence between the condition of lithology and the measured gas concentration in lithology and lithology boundaries, but there is an influence between geological structure and mercury gas concentration. Based from the spatial distribution map of mercury gas concentrations, there are five potential zones that are in the PA03 area towards PA04, PPL05, PPL06, PPL07, and PPL08.